Isolation and high‐dimensional phenotyping of gastrointestinal immune cells. Issue 1 (20th February 2017) - David, Bruna A.; Rubino, Stephen; Moreira, Thais G.; Freitas‐Lopes, Maria Alice; Araújo, Alan M.; Paul, Nicole E.; Rezende, Rafael M.; Menezes, Gustavo B.
Summary: The gastrointestinal immune system plays a pivotal role in the host relationship with food antigens, the homeostatic microbiome and enteric pathogens. Here, we describe how to collect and process liver and intestinal samples to efficiently isolate and analyse resident immune cells. Furthermore, we describe a step‐by‐step methodology showing how to high‐dimensionally immunophenotype resident leucocytes using cytometry by time‐of‐flight, providing a well‐characterized antibody platform that allows the identification of every leucocyte subset simultaneously. This protocol also includes instructions to purify and cultivate primary murine hepatocytes, a powerful tool to assess basic cell biology and toxicology assays. Gut and liver samples from the same mouse can be collected, processed and stained in less than 6 hr. This protocol enables the recovery of several populations of purified and viable immune cells from solid and fibrous organs, preventing unwanted loss of adherent cells during isolation. Abstract : A protocol to isolate viable immune cells from gut lamina propria and liver, and a high‐dimensional analysis of cell immunophenotyping using mass cytomety (CyTOF) are described.